Impact of dynamic physical exercise on high‐risk definite arrhythmogenic right ventricular cardiomyopathy. (23rd August 2018) - Ruiz Salas, Amalio; Barrera Cordero, Alberto; Navarro‐Arce, Isabel; Jiménez Navarro, Manuel; García Pinilla, José Manuel; Cabrera Bueno, Fernando; Abdeselam‐Mohamed, Nasiba; Morcillo‐Hidalgo, Luis; Gómez Doblas, Juan José; de Teresa, Eduardo; Alzueta, Javier
Abstract: Introduction: Arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D) is an inherited cardiomyopathy characterized by ventricular arrhythmias and heart failure. The variable phenotype suggesting that determined environmental factors may have an influence. The aim of our study was to discover the impact of the dynamic physical activity on patients with high‐risk definite ARVC/D. Methods and Results: Collection of data on physical activity at the time of diagnosis was conducted at an in‐person clinical interview. The intensity of the activity was classified in accordance with the mean frequency of weekly physical exercise sessions in the 10 years before diagnosis and into the following three groups of dynamic activity: high/competitive (>3 h/wk), moderate (1 to 3 h) and minimal/inactive (<1 h). Seventeen patients practiced high dynamic physical activities. The intensity of dynamic activity was classified into three groups: 8 of high intensity, 9 moderate, and 19 inactive. The first major arrhythmic event and occurrence of severe right ventricular dysfunction were earlier in the high‐intensity exercise group, followed by the moderate intensity group and at a later age in the low‐intensity/inactive group. Conclusions: Dynamic exercise could be directly associated with the severity of the phenotype in relation to the precocity of major ventricular arrhythmic events and right ventricular systolic dysfunction in patients with high‐risk definite ARVC/D.